Engagement Pustakawan Dengan Pemustaka Melalui Instagram Perpustakaan PTKI Medan - Sitanggang, Marianna (Ikatan Pustakawan Indonesia, 2023)
Libraries need to increase engagement rate on Instagram by having a strategy to increase engagement with their followers. There are many indicators of successful engagement rate by measuring likes, comments and shares. It takes personnel who have the ability and competence in managing Instagram. This is usually done by a librarian who is usually the person who manages the activities in the library. Then the librarian must have the ability, expertise and skills in managing Instagram accounts. This study aims to determine the engagement of librarians with users through social media Instagram owned by the PTKI Medan Library. User involvement through various reactions is needed to strengthen user relationships, increase user retention, and loyalty to the library. This study used descriptive qualitative method. Data analysis used descriptive statistics. The results of this study indicate that the Engagement Rate of the PTKI Medan Library's Instagram Account grew from 23.8% to 24.4%. The engagement of librarians with users on the PTKI Medan Library Instagram account 23.8% is very good. This means that Instagram accounts are seen by users and really like Instagram content and are encouraged to interact continuously.